Prognosis and Chances of Recovery in Bell's Palsy - Niccolò Fagni; Ferdinando Paternostro; Jacopo Junio Valerio Branca; Lorenzo Salerni; Marco Mandalà (Infermieristica Journal)
The Bell’s palsy was firstly described about two century ago by the neuroanatomist Charles Bell. This paralysis affects the VII cranial nerve and, up to date, the aetiology of the disease appears to be multifactorial. In the present manuscript, focusing on the anatomical structures related to the VII nerve, such as its the stapedial muscle innervation, we highlight the role of impedance testing as a helpful examination for the facial nerve function, together with its role as effective and safe prognosis in Bell’s palsy by the stapedial reflex.